2013
DOI: 10.1080/01496395.2013.820759
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension Analysis of Flocs in Inline Coagulation-Microfiltration of Natural Organic Matter (NOM)

Abstract: Technology (NTNU), Norway2D fractal dimension analysis of inline-coagulation (IC) flocs in microfiltration of NOM using power-law relationship and boxcounting was done. Different process conditions represented by two types of coagulants (PIX and PAX) at four different hydraulic gradients (G-values of 4, 31, 98, and 300 s À1 ) were tested. Fractal dimensions of the flocs formed under the varying process conditions were found to be different. Overall NOM removal was found to be similar for all cases; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The floc property mainly includes floc size and compactness, which can be investigated by combining the light scattering or image technique with fractal theory (Gungoren et al, 2020). The filter cake property can be characterized by observation techniques such as scanning electron microscope (SEM) and X-ray microtomographic techniques (Thapa et al, 2009;Lin and Miller, 2000;Raspati et al, 2013). However, contradictory conclusions are obtained regarding the effects of floc properties on filtration performance (Fitria et al, 2013;Cao et al, 2016), because both floc size and compactness significantly affect the filtration process, and it is difficult to predict which one is dominant.…”
Section: Introductionmentioning
confidence: 99%
“…The floc property mainly includes floc size and compactness, which can be investigated by combining the light scattering or image technique with fractal theory (Gungoren et al, 2020). The filter cake property can be characterized by observation techniques such as scanning electron microscope (SEM) and X-ray microtomographic techniques (Thapa et al, 2009;Lin and Miller, 2000;Raspati et al, 2013). However, contradictory conclusions are obtained regarding the effects of floc properties on filtration performance (Fitria et al, 2013;Cao et al, 2016), because both floc size and compactness significantly affect the filtration process, and it is difficult to predict which one is dominant.…”
Section: Introductionmentioning
confidence: 99%
“…Their results confirmed that there is a distinct effect of dosage on floc size. Raspati et al [55] investigated the influence of two coagulants under different mixing conditions on the fractal dimensions of flocs formed via in-line coagulation of NOM prior to microfiltration. They concluded that these floc parameters could be helpful in membrane fouling elucidation.…”
Section: Feed-backward Control Based On Dosed Water Qualitymentioning
confidence: 99%